Effect of Preprocessing Storage Temperature and Time on the Physicochemical Properties of Winter Melon Juice - Xiuxiu Sun; Elizabeth A. Baldwin; John Manthey; Christina Dorado; Ted Rivera; Jinhe Bai (Journal of Food Quality)
Numerous studies demonstrated that winter melons (Benincasa hispida) have a long storage life at 20°C without quality and flavor degradation in fruit. However, fruit for processing are frequently handled under refrigerated conditions or exposed to a warehouse without air conditioning. Therefore, this research aimed to evaluate whether a short high- and low-temperature storage of fruit, prior to processing, changes the flavor and nutritional profiles of winter melon juice. Weight loss of 1.71% was recorded subsequent to 20 days of 10°C storage, with 5.15% weight loss at 30°C. Sugar content significantly decreased during storage at 10°C and 30°C, while the soluble solids content slightly increased. Several specific phenolic compounds were detected, and the total concentration of phenolics increased over the storage time at both temperatures. The concentration of sulfur compounds, as well as hexanal and total volatiles that are principally responsible for off-flavor reduced significantly during storage and the reduction was greater at 10°C than at 30°C. The results indicate that preprocessing fruit storage at 10 or 30°C for 20 days will not harm the quality and flavor of winter melon juice. However, longer storage time caused water-soaked spots at 10°C and dry rot at 30°C.